Kurikulum Pendidikan Islam Persektif Alghazali dan Ahmad Tafsir - FADLI, MUHAMMAD; Mafrukhin, Usman (Mu'allim, 2025)
This article aims to find out how the curriculum according to the figures, namely Imam Ghozali and Ahmad Tafsir. Hopefully, the curriculum of this figure can be used as a reference or reference to the existing curriculum. The method used in this research uses library research by looking for reference sources that are relevant to the curriculum and Islamic curriculum. The results of this study indicate that Imam Ghozali and Ahmad Tafsir both have a comprehensive view of the curriculum, especially in the Islamic curriculum. From each view, it is also detailed how the curriculum can be implemented from the basic level to the upper level. Furthermore, the procedures in the division of curriculum and methods are also explained in detail.